Clinical results of and prospects for the use of controlled-release antiepileptic drugs: a new once-daily levetiracetam formulation - P. N. Vlasov (Неврология, нейропсихиатрия, психосоматика)
Many antiepileptic drugs (AEDs) have a short half-life (T1/2) with a wide fluctuation from peak to trough blood concentrations. According to this pharmacokinetic profile, there may be both adverse events (AEs) due to the increase in a blood drug concentrations and seizures as a result of its fall, which ultimately lowers patient adherence to therapy.Pharmaceutical technologies ensuring a delayed release of the active ingredient can make the concentration of a drug more stable and therefore reduce the frequency and severity of AEs, enhance the efficiency of therapy, compliance, and retention of the patient on AEDs. The emergence of a new sustained-release levetiracetam formulation in neurologists' practice greatly enhances the possibilities of epilepsy therapy.